1996
DOI: 10.2337/diab.45.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Puberty on Markers of Glomerular Hypertrophy and Hypertension in IDDM

Abstract: Epidemiological data implicate puberty as a factor in the initiation of diabetic nephropathy. However, the mechanism remains unclear. We hypothesized that puberty would result in an increase in glomerular hypertrophy and hypertension; these two early concomitant events are seen as pivotal to the pathophysiology of diabetic nephropathy. We studied the effect of pubertal duration on three surrogate markers of glomerular hypertrophy/hypertension: kidney volume (KV), microalbuminuria (MA), and Na-Li countertranspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 38 publications
2
51
0
3
Order By: Relevance
“…proliferative retinopathy [3]. Diabetic end-organ complications rarely occur before puberty, and the onset of puberty accelerates microvascular complications [4][5][6][7]. These observations suggest an association between sex hormones and diabetic end-organ complications.…”
Section: Introductionmentioning
confidence: 78%
“…proliferative retinopathy [3]. Diabetic end-organ complications rarely occur before puberty, and the onset of puberty accelerates microvascular complications [4][5][6][7]. These observations suggest an association between sex hormones and diabetic end-organ complications.…”
Section: Introductionmentioning
confidence: 78%
“…A cross-sectional study of 177 adolescents with type 1 diabetes showed that renal enlargement is associated with microalbuminuria as well as with pubertal duration [50]. Participants with kidney volume >300 ml/1.73 m 2 were eight times more likely to have microalbuminuria than those with kidney volume <300 ml/1.73 m 2 .…”
Section: Hyperfiltration and Nephromegalymentioning
confidence: 99%
“…Em relação à terapêutica, a dose diária de insulina foi semelhante à observada em outras séries (9,25,26). Apesar da dose não ter diferença significativa entre os pacientes nos diferentes estágios de Tanner que pode ser justificado pelo tamanho da amostra, observamos uma tendência ao uso de maiores doses durante a puberdade, confirmando dados de literatura (27).…”
Section: Discussionunclassified
“…No nosso meio a grande miscigenação racial não nos permitiu categorizar os pacientes dificultando uma análise comparativa. Na análise estratificada em pré-púberes, púberes e adultos os níveis de HbA 1C não foram associados ao sexo em pré-púberes e adultos, semelhante a outros relatos da literatura (19,26). Como descrito em estudo multicêntrico europeu (27), os maiores níveis de HbA 1C foram observados em púberes do sexo feminino, diferente do relatado em uma série da Bélgica (25).…”
Section: Discussionunclassified
See 1 more Smart Citation